Using COBIT4.1 in Evaluating Hospital ITG Implementation - BAHARI, ASNIATI (Jurnal Akuntansi dan Governance Andalas, 2018)
This research has an intention to evaluate the implementation of IT governance in a private hospital (Hospital X) in Padang city by using COBIT 4.1 framework; and to recommend IT governance practices that can improve IT governance at the hospital in the future. COBIT 4.1 provides model of processes found in IT activities in 4 domain, Plan and Organize (PO), Acquire and Implement (AI), Deliver and Support (DS), and Monitor and Evaluate (ME). Data were collected by using document evaluation, interview and observations. The result showed that IT governance implementation at the hospital has not achieved the best practice yet. The existence of activities related to IT governance is defined, but inconsistency still happens. There are 28 IT processes out of 34 IT processes and 110 detailed control objectives exist out of 210 detailed control objectives. The identified IT processes show the existing IT activities in the hospital support the achievement of its strategy and objectives. Control objectives of each IT process needs to be implemented for more effective process. The hospital should optimize the practices of each IT process for optimal results.